Penerapan Algoritma Backprogation Untuk Memprediksi Tingkat Kerawanan Banjir di Wilayah Kabupaten Mandailing Natal - Putriyani Matondang; Saifullah Saifullah; Jaya Tata Hardinata (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The purpose of this study was to determine the flood vulnerability in the Mandailing Natal Regency. In this study, researchers used the Artificial Neural Network method with the Backprogation algorithm. Artificial neural network method is a method that is able to perform mathematical processes to predict flood-prone areas with backprogation algorithms for data management that is applied by matlap. The data source used is direct observation in the area of Mandailing Natal Regency. The data will be managed based on flood disasters that occur every year. The results obtained from the test are performance and epoch values where each architecture is not the same, the test results are displayed in the form of a graph comparing the target value with the training and testing process.